(untitled) (PROKLA. Journal of Critical Social Science, 2011)
By widening noticeably their frame of activities NATO troops have been intervening in the internal conflicts of Afghanistan for a decade, following geopolitical and economic interests. They have met enormous obstacles through guerilla warfare and the loose tribal and administrative structures of the country. The Taliban operate with national and religious motives and can count on considerable support from the population. Since no side will presumably score a decisive victory, the probable solution will be a compromise allowing the coexistence of the insurgents with the Kabul-administration, as well as being compatible with the interests of the adjacent states.